Disadvantaged early-life experience negatively predicts prosocial behavior: The roles of Honesty-Humility and dispositional trust among Chinese adolescents. (1st January 2020) - Wu, Junhui; Yuan, Mingliang; Kou, Yu
Abstract: Early-life experience affects individuals' lifelong development in various domains. In this research, we examine how early-life experience affects adolescents' prosocial behavior using a large-scale survey among 2, 975 Chinese senior high school students (47.6% boys, M age  = 16.12 years). We operationalize disadvantaged early-life experience as having unpredictable and resource-scarce environments, and distant parent-child relationships in childhood. Findings suggest that disadvantaged early-life experience negatively predicts adolescents' self-reported prosocial behavior and prosociality in a resource allocation task. Moreover, this observed relation between early-life experience and prosocial behavior is explained by Honesty-Humility and dispositional trust. Specifically, adolescents who experience more unpredictability, resource scarcity, and distant parent-child relationships during childhood display lower levels of Honesty-Humility and dispositional trust in others, and thus behave less prosocially. Notably, Honesty-Humility does not mediate the relation between early-life experience and self-reported prosocial behavior, and only significantly predicts boys' prosocial behavior. These findings emphasize that creating benign early rearing environments can facilitate individuals to develop prosocial traits and behaviors later in life. Highlights: This study ( N  = 2, 975) tests how early-life experience affects prosocial behavior. Disadvantaged early-life experience undermines adolescents' prosocial behavior. This observed effect is mediated by Honesty-Humility and dispositional trust. Honesty-Humility does not mediate the effect on self-reported prosocial behavior. Honesty-Humility only significantly predicts adolescent boys' prosocial behavior.